2021
DOI: 10.1038/s41598-021-00622-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning models for screening of high myopia using optical coherence tomography

Abstract: This study aimed to validate and evaluate deep learning (DL) models for screening of high myopia using spectral-domain optical coherence tomography (OCT). This retrospective cross-sectional study included 690 eyes in 492 patients with OCT images and axial length measurement. Eyes were divided into three groups based on axial length: a “normal group,” a “high myopia group,” and an “other retinal disease” group. The researchers trained and validated three DL models to classify the three groups based on horizonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Machine learning and deep learning have been successfully applied in OCT images for biomarker identification in AMD (24). Since myopia is a rising problem in ophthalmology, OCT images have been used for AI prediction in myopic eyes recently (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning and deep learning have been successfully applied in OCT images for biomarker identification in AMD (24). Since myopia is a rising problem in ophthalmology, OCT images have been used for AI prediction in myopic eyes recently (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also involved auto-detection of myopic macular diseases using AI algorithm due to the rising prevalence of myopia and multiple vision-threatening retinal damages ( Sogawa et al, 2020 ; Choi et al, 2021 ; Ye et al, 2021 ; Li et al, 2022a ). Ye et al (2021 ) engineered the deep-learning (DL) model to identify myopic maculopathy, including macular choroidal thinning, macular Bruch membrane (BM) defects, sub-retinal hyper-reflective material (SHRM), myopic traction maculopathy (MTM), and dome-shaped macula (DSM), and the result showed that the AUC was 0.927–0.974 for five myopic maculopathies.…”
Section: Discussionmentioning
confidence: 99%
“… Ye et al (2021 ) engineered the deep-learning (DL) model to identify myopic maculopathy, including macular choroidal thinning, macular Bruch membrane (BM) defects, sub-retinal hyper-reflective material (SHRM), myopic traction maculopathy (MTM), and dome-shaped macula (DSM), and the result showed that the AUC was 0.927–0.974 for five myopic maculopathies. Choi et al (2021 ) trained and validated three DL models to identify myopia and generated a result of the absolute agreement with retina specialists which was 99.11%. However, the specific lesion associated with myopia could not be detected, and validation with an external dataset was needed.…”
Section: Discussionmentioning
confidence: 99%
“…It was natural to come up with a deep learning model architecture that takes both POS and NEG images within a cycle simultaneously as inputs because clinicians can obtain information from dynamic movements of TM between those images (Cho et al 2009; Lee et al 2011). As a method of feeding multiple images in parallel into a deep learning model, a multi-column CNN has been suggested and showed its effectiveness (Ciresan et al 2012; Zhang et al 2016; Jin et al 2019; Choi et al 2021). Therefore, we devised multi-column CNN models to train both POS and NEG images simultaneously, where the features from dynamic input images of each column are abstracted independently and combined by various arithmetic operations (concatenate, summation, or subtraction) at the near-endpoint.…”
Section: Methodsmentioning
confidence: 99%